Marine Observing Applications Using AIS: Automatic Identification System - Wright, Darren; Janzen, Carol; Bochenek, Robert; Austin, Jessica; Page, Edward (Frontiers in Marine Science, 2019)
The Automatic Identification System (AIS) is a real-time network of transmitters and receivers that allow vessel movements to be broadcast, tracked and recorded. Though traditionally used for real-time maritime applications related to keeping track of vessel traffic for collision avoidance, there is increasing interest in using AIS data and the AIS platform for maritime safety planning, resource management and weather forecasting. AIS data are being made tractable for alternative non-real-time applications like determining trends and patterns in vessel traffic and helping to prioritize where modern bathymetric surveys are needed to ensure safe maritime transit. The AIS is also being used for widespread transmission of critical environmental conditions information, such as sea state and weather, to mariners, forecasters and emergency response providers. Several pilot projects are underway that demonstrate the capacity and promise of AIS data and the AIS platform to serve multiple purposes, providing overall maritime domain awareness while maintaining its most important objective of tracking vessels.